2018
DOI: 10.5296/ijhrs.v8i3.13213
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Intention: Does Entrepreneurial Education Matter in Pakistan?

Abstract: The purpose of this study is to investigate the association between entrepreneurial intention and entrepreneurial education. Data were collected with the help of a structure questionnaire; a total 595 responses were collected back. SmartPLS was used to test the hypothesized relationship. The findings showed that entrepreneurial intentions are strongly and positively related to entrepreneurial education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 36 publications
(44 reference statements)
0
24
0
1
Order By: Relevance
“…This is because passion shows how entrepreneurs are willing to spend time and effort to make the business successful. Entrepreneurs can be more persuasive when they show high levels when positive and confidence (Anjum et al 2018a;Obschonka et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because passion shows how entrepreneurs are willing to spend time and effort to make the business successful. Entrepreneurs can be more persuasive when they show high levels when positive and confidence (Anjum et al 2018a;Obschonka et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For developing economies, mainly developing Asian economies, there is a scarcity of research on the relationship between EI with PUS (Nabi et al 2017). Anjum et al (2018a) and Turker and Selcuk (2009) believe that entrepreneurship education, especially the university education system, plays a vital part in the growth of students' entrepreneurial intentions.…”
Section: The Moderating Role Of Perception Of University Supportmentioning
confidence: 99%
“…The researchers collected the completed questionnaire several days after it was distributed. Partial least square structural equation modeling (PLS-SEM) was used for data analysis in the current study, as proven in similar prior research [77]- [80]. Measurements of all items were achieved using a 5-point Likert scale (ranging from 1 = "Strongly Disagree" to 5 = "Strongly Agree").…”
Section: Methodsmentioning
confidence: 99%
“…students) to verify the EI literature (Cardon et al, 2009;Karimi et al, 2017). Several empirical studies have also demonstrated the positive impact of EP on business behavior and performance (Anjum et al, 2019;Murnieks et al, 2014). While there is considerable progress in valuing the importance and impact of EP, the extent of EP in influencing new companies' ambitions must be addressed.…”
Section: Entrepreneurship Passion (Inventing and Founding) And Entrep...mentioning
confidence: 98%